Optimization of Nanobubble-Assisted Bunker Oil Flotation from Oil-Wet Sand via Response Surface Methodology (RSM) - Wei, Lim Mee; Von, Lau Ee; Eong, Poh Phaik (ASEAN Journal of Chemical Engineering, 2015)
Flotation technology is an effective method for the separation of oil from sand via gas-liquid-solid system. The mechanism of flotation lies in the generation of gas bubble that attaches itself to the hydrophobic particles. Therefore, one of the main parameters which could affect the efficiency of flotation is the bubble size distribution. This research aims to investigate the efficiency of nanobubbles (NBs) in the flotation process to remove high density bunker oil from oil/sand slurry in a laboratory-scale flotation cell. Experiments were carried out using NBs (approximate diameter of 200 nm) generated via ultrasonication for the flotation studies. In this investigation, four different variables including amplitude (sonication power), pH, duration of sonication (min) and input flowrate of NBs (ml/s) were studied. The second order response function was used for obtaining flotation efficiency, and was further optimized using response surface methodology (RSM) to maximize flotation efficiency within the experimentally studied range. The optimum parameters were found to be, 70% amplitude, pH 12, 10 min of flotation and an input flowrate of 57 ml/s to achieve the predicted maximum flotation efficiency of 19.83%. This was in agreement to the experimental results which show an optimum flotation efficiency of 19.98%. The test results indicated that the use of NBs alone provided unsatisfactory flotation. Even though NBs (larger surface area) are expected to increase the bubble-particle attachment and decrease the detachment probabilities, the low buoyancy/low rising velocity of NBs prevents efficient flotation despite the advantages they have. Future studies would include the optimization of bubble size to improve the flotation efficiency